"I remember…so, let's not forget": remembering our past lest we repeat it. Issue 4 (1st October 2020) - Mosher, James K.
ABSTRACT: What happens when we, as a profession, forget our past, whether it is what history and research have taught or the values that motivated us to become healers? Here, I explore this question. First, I remember several experiences I have had that illustrate what can go wrong when we "forget." Then, I review some of our history and research, critically examining it, to remind us of those lessons. Finally, I share examples from my own practice to show how remembering the past can guide us in the present.